2005
DOI: 10.1007/s10979-005-3613-2
|View full text |Cite
|
Sign up to set email alerts
|

Legal Decisions of Preadolescent and Adolescent Defendants: Predictors of Confessions, Pleas, Communication with Attorneys, and Appeals.

Abstract: While there is an increasing recognition that developmental differences may exist in legal decision-making, little research has examined this. This study examined the legal judgments of 152 defendants aged 11-17 (73 females, 79 males). Adolescents aged 15 and younger were more likely than older adolescents to confess and waive their right to counsel, and less likely to report that they would appeal their case or discuss disagreements with their attorneys. Also, while adolescents aged 15-17 were more likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
179
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(193 citation statements)
references
References 48 publications
12
179
1
1
Order By: Relevance
“…This sample has been described in other studies that have examined other aspects of juveniles' competence (Viljoen, Klaver, & Roesch, 2005;. The majority of defendants remanded to this facility were 15 and older.…”
Section: Methods Participantsmentioning
confidence: 99%
“…This sample has been described in other studies that have examined other aspects of juveniles' competence (Viljoen, Klaver, & Roesch, 2005;. The majority of defendants remanded to this facility were 15 and older.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Viljoen et al (2005) reported that adolescent defendants planning to plead guilty were more likely to have been advised to do so by their attorneys than were adolescents who planned to plead not guilty.…”
mentioning
confidence: 99%
“…Birçok laboratuvar ve alan çalışmasında yaşı küçük ergenlerin yaşı büyük ergenlere ve yetişkinlere göre, yaşı büyük ergenlerin ise yetişkinlere göre yasal süreçleri daha az anladıkları ve adli süreçlerde kendilerini daha yetersiz savundukları (Grisso ve ark., 2003;Redlich, Silverman ve Steiner, 2003), verilen cezalara daha az itiraz ettikleri ve sorguladıkları (Redlich ve Goodman, 2003), sorgudaki davranışlarının sonuçlarını daha zayıf öngörebildikleri (Grisso ve ark., 2003;Redlich ve ark., 2003) ve bu yetersizliklerin etkisiyle daha çok sahte itirafta bulundukları gözlenmektedir. Bu bulguları destekler biçimde, soruşturma geçiren yaşı küçük ergenlerin yaşı büyük ergenlere göre susma hakkını kullanma, avukat isteme ve dava sonucuna itiraz etme gibi yasal haklarına daha az başvurdukları ve daha çok itirafta bulundukları rapor edilmektedir (Viljoen, Klaver ve Roesch, 2005).…”
Section: A)yaşunclassified